Evaluation of Hematological Alterations Associated with Arthritis among Individuals in Karbala City - Hasan Ali Alsailawi (Journal of Microbiology, Biotechnology and Conservation, 2026)
Arthritis can cause measurable hematological changes (anemia, leukocyte and platelet alterations, raised acute-phase markers). The current study aimed to evaluate hematological alterations among individuals diagnosed with arthritis in Karbala City and to compare these parameters with age- and sex-matched controls. Cross-sectional study enrolling adults (≥25 years) with clinical diagnosis of arthritis presenting to rheumatology/orthopedic clinics in Karbala Imam Hussein Medical City, Karbala Teaching Hospital for Children, and some health centers and private laboratories in Karbala Governorate during the period from December 20, 2022 to April 10, 2023, where (20). Controls: healthy volunteers matched by age and sex. Hematological tests: complete blood count (CBC) with indices, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and when available rheumatoid factor (RF) and anti-CCP. Demographics, clinical features, disease duration, and medication history collected. Primary outcomes: prevalence of anemia, leukocytosis/leukopenia, thrombocytosis/thrombocytopenia, and correlations with ESR/CRP. Statistical tests: t-test / Mann-Whitney U, chi-square, Pearson/Spearman correlation, multivariable linear/logistic regression. Significance p<0.05. (placeholder-insert observed frequencies, means, and key p-values.) (placeholder-summarise main hematological alterations found and clinical implications for diagnosis/management in Karbala.)